ANALYTICAL ANALYSIS OF THE OPTIMAL DIMENSIONS AND ENERGY PARAMETERS OF THE IMPELLER OF A NOZZLE HYDRAULIC TURBINE - Begmatov, Eldorjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. This article reflects the importance of low-pressure micro hydropower plants today, information about the problems, causes and ways to solve them. The problems of micro hydroelectric power stations continue to be studied all over the world. Opinions and recommendations are important because the scientific works and literature of about 20 world scientists and researchers were studied as sources, as well as scientific information. Methods. About 20 literatures have been studied, which consider the design of microhydroelectric power plants operating in low-pressure water sources, the factors causing power losses in them. Based on the research results, the energy relationships between their constructive and geometric dimensions are analyzed. Factors affecting efficiency were calculated. Results. Based on the analysis of the literature, calculations were made for the impeller of the turbine of a microhydroelectric power station. The number of nozzles in the turbine, the angle of inclination, the number of guide vanes, the central angle between the guide vanes, the water flow rate, the diameter of the guide device, the feed cylinder, the taper angle at which the water flow rate is the least energy in flat compression. The calculations were revised by introducing boundary conditions for several options. It has been established that when the radius R2 of the guiding cylinder is equal to the radius of the supply cylinder, the energy losses for energy expansion (compression) are minimal. It was found that the diameter of the impeller of a hydraulic turbine can be changed to fit the size of the nozzle, however, an increase in the diameter leads to an increase in the moment of inertia about its center and a sharp decrease in the rotational speed . The water intakes of the hydraulic turbine feed cylinder and the nozzle are made round, and the ratio between their surfaces is analyzed. Conclusions. The diameter of the water supply cylinder of the hydroturbine has been increased in places where it is planned to work in sources with high water consumption and low pressure. This situation leads to an increase in the diameter of the impeller. Exceeding the critical value of the impeller diameter leads to an increase in the moment of inertia and a decrease in the speed of the impeller. This, in turn, leads to excessive energy losses due to the use of additional pulleys or gearboxes.